2016
DOI: 10.1007/s00706-016-1785-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polybrominated benzimidazole and benzotriazole derivatives containing a tetrazole ring and their cytotoxic activity

Abstract: A series of new benzimidazole and benzotriazole derivatives containing a tetrazole moiety was synthesized by N-alkylation of 5-aryltetrazole with 4,5,6,7-tetrabromo-1-(3-chloropropyl)-1H-benzimidazole and 4,5,6,7-tetrabromo-2-(3-chloropropyl)-2H-benzotriazole. The reaction was regioselective and mostly 2,5-disubstituted tetrazole derivatives were obtained. The effect of all synthesized compounds on human recombinant casein kinase 2alpha subunit (rhCK2α) and cytotoxicity against human T-cell lymphoblast (CCRF-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Pett et al reported diamino polyamide 598a–c with an alkyl amino group at the N1 position of the imidazole/pyrrole ring and assayed for modulation of topo IIα and inhibition of NF‐Y binding. Chojnacka et al synthesized benzimidazole and benzotriazole derivatives containing (Scheme ) tetrazole moiety through N ‐alkylation of 5‐aryltetrazole with 4,5,6,7‐tetrabromo‐1‐(3‐chloropropyl)‐1 H ‐benzimidazole and 4,5,6,7‐tetrabromo‐2‐(3‐chloropropyl)‐2 H ‐benzotriazole in which compounds 601 and 603 showed most potent anticancer results against CCRF‐CEM and MCF‐7 cell lines. Nayak et al reported 2‐aryl benzimidazole conjugates and assayed them against MCF‐7 cell lines for anticancer activity.…”
Section: Pharmacological and Synthetic Profiles Of Benzimidazole Derimentioning
confidence: 99%
See 1 more Smart Citation
“…Pett et al reported diamino polyamide 598a–c with an alkyl amino group at the N1 position of the imidazole/pyrrole ring and assayed for modulation of topo IIα and inhibition of NF‐Y binding. Chojnacka et al synthesized benzimidazole and benzotriazole derivatives containing (Scheme ) tetrazole moiety through N ‐alkylation of 5‐aryltetrazole with 4,5,6,7‐tetrabromo‐1‐(3‐chloropropyl)‐1 H ‐benzimidazole and 4,5,6,7‐tetrabromo‐2‐(3‐chloropropyl)‐2 H ‐benzotriazole in which compounds 601 and 603 showed most potent anticancer results against CCRF‐CEM and MCF‐7 cell lines. Nayak et al reported 2‐aryl benzimidazole conjugates and assayed them against MCF‐7 cell lines for anticancer activity.…”
Section: Pharmacological and Synthetic Profiles Of Benzimidazole Derimentioning
confidence: 99%
“…Chojnacka et al[120] synthesized benzimidazole and benzotriazole derivatives containing (Scheme 102) tetrazole moiety through N-alkylation of 5-aryltetrazole with 4,5,6,7-tetrabromo-1-(3-chloropropyl)-1H-benzimidazole and 4,5,6,7-tetrabromo-2-(3-chloropropyl)-2H-benzotriazole in which compounds 601 and 603 showed most potent anticancer results against CCRF-CEM and MCF-7 cell lines. Nayak et al[121] reported 2-aryl benzimidazole conjugates and assayed them against MCF-7 cell lines for anticancer activity.…”
mentioning
confidence: 99%
“…[15][16][17][18] In recent years, many research groups focused on the synthesis and anti-cancer properties of hybrid compounds of coumarin with other bio-active heterocyclic moieties such as pyrimidine, 19 chalcone, 20 βcarboline, 21 indole-triazole, 22 artemisinin, 23 thiazole, 24 and isooxazilones. 25 In the meantime, hybrid compounds of benzimidazole and their anticancer properties were reported with various heterocyclic moieties such as triazine, 26 ellipticine, 27 tetrazine, 28 deoxynucleosides, 29 thiazoles, 30 and chrysin. 31 However, according to our literature survey, coumarin-benzimidazole hybrids are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…A series of 4,5,6,7‐tetra‐ bromo‐2‐(3‐chloropropyl)‐ 2H ‐benzotriazole derivatives were synthesized in 2016. The effect of these compounds on human recombinant casein kinase 2α subunit (rhCK2α) and significant cytotoxicity against human T‐cell lymphoblast (CCRF‐CEM) and breast adenocarcinoma (MCF‐7) cell lines had been reported . Regioisomeric BTAs on the different nitrogen atoms are difficult to be synthesized and their anticancer properties remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of these compounds on human recombinant casein kinase 2α subunit (rhCK2α) and significant cytotoxicity against human T-cell lymphoblast (CCRF-CEM) and breast adenocarcinoma (MCF-7) cell lines had been reported. [16] Regioisomeric BTAs on the different nitrogen atoms are difficult to be synthesized and their anticancer properties remain poorly defined. In this work, we aimed to design novel molecules that can be used as inhibitors of PTKs with anticancer properties by fragment-based design strategy.…”
Section: Introductionmentioning
confidence: 99%